Planktonic rotifers of a saline-lowland river : The Salado River (Argentina) - Neschuk, Nancy Carolina (2002)
Seasonal samples of zooplankton were taken during 1997-1999 at fifteen stations in the Salado River basin, and analysed in order to study the rotifer fauna. Spatio-temporal changes in the rotifer plankton composition were examined in the main channel and its tributaries. The majority of species found are tolerant of a wide range of pH, whereas others prefer neutral to alkaline values. The total rotifer plankton density increased downstream from the headwaters to the middle sector of the river. The associated shallow lakes and tributaries were an important source of species. Variations in density and number of species were shown to be associated with conductivity, and species tolerant of high conductivity conditions were especially prevalent (upper 7,000 μS cm-1). Rotifer density was influenced by hydrological conditions, which promoted maximum values during low water periods and in the high water condition promoted the incorporation of species from shallow lakes connected with the river during flood events. The species associations found are related to such water parameters as conductivity and nutrient availability and to the presence of ponds and shallow, waterlogged depressions connected in varying extent to the main channel.